PENGEMBANGAN MEDIA CHATBOT SCAFFOLDING UNTUK MENDUKUNG PEMBELAJARAN PROJECT BASED LEARNING SECARA DARING - Sofnidar Sofnidar; Khairul Anwar; Parida Anum (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to produce chatbot scaffolding media with a PjBL model in e-lematika to improve student learning outcomes in class VIII Cartesian cooordinat material that is appropriate for use in the learning process. This research is a development research using the ADDIE model which consist of 5 stages, namely analyze, design, development, implementation and evaluation. There are three criteria used to measure the quality of chatbot scaffolding media, namely 10 valid, the validity of the media is obtained from validation tests by material experts and design experts. 2) practical, the practicality of the media is obtained from the teacher’s practicality questionnaire and student practicality questionaire and 3) effective, the effectiveness of the media is obtained from the student response questionnaire and student learning achievement tests. The result of this study indicate that: 1) the result of the percentage validity of material experts are 96.36% (very valid). and design experts are 86.66% (valid); 2) the percentage of practicality by educators is 72.50% (practical) and by students 75.05% (practical); 3) the percentage of the effectiveness seen form the student response questionnaire 75.09% (effective) and the persentageof the completeness of student learning outcomes is 81.25% (very good).